Pandangan golongan dewasa di daerah-daerah terpilih negeri Kedah terhadap hak kebebasan bersuara - Omar, Rusdi (Universiti Utara Malaysia, 2005)
On August 20, 2001, The Human Rights Commission of Malaysia better known as Suhakam, issued an official report on the handling by the police of a public assembly organised by opposition parties at Kesas Highway and Kebun Road on Novembers 5, 2000. The report pointed to the fact that there have been some human rights violation committed by the police in their handling of the assembly. The former Malaysian Prime Minister, Tun Dr. Mahathir Mohamad on the following day criticised the organisation and accused the report as "biased and influenced by western thought", and thus is against the national interest. In this context, the concept of freedom of speech during the assembly may be presumed as a "western idea" and thus may not be an appropriate concept to be practised in Malaysia. The aim of this article is to highlight the concept of freedom of speech in Malaysia, particularly in the state of Kedah, seen from various perspectives such as law, political culture,media, government and the society in general. The article is based on the findings of a study conducted on members of the public and private sectors,as well as members of the various trade unions in Kedah, namely in Alor Setar, Kubang Pasu, Sungai Petani and Pendang. The result of this study indicated that the people of Kedah are in favour ofa greater freedom of speech without any obstruction by thegovernment through legislative controls. The respondents believe that the existing rights should be expanded for the sake common interest. They however do not believe in absolutefreedom of speech.There should be some limitations imposed but they should not be as restrictive as they are now. Undoubtedly, there is a growing awareness among the population of the importance of the human rights andfreedom of expression concepts to be nurtured for democracy to work in a credible and more meaningful manner in this country.